Profil Candida penyebab kandidemia dan pola kepekaan terhadap anti jamur pada pasien sakit kritis di Rumah Sakit Cipto Mangunkusuno - Mursinah, Mursinah; Ibrahim, Fera; Wahid, Mardiastuti (Puslitbang Biomedis dan Teknologi Dasar Kesehatan, 2016)
Candida spesies is important cause of nosocomial infection that lead to death and prolonged hospital stay. Guideline management of candidiasis by Infectious Diseases Society of America (IDSA) in 2009 proposed early antifungal therapy in critical patient with the risk of invasive candidiasis. Early identification of sepsis patien with high risk of fungal infection is challenging because long and low result from blood culture. Antifungal usage without appropriate indication can cause resistance to antifungal. The aim of the study is obtain data candida species that caused candidemia in Cipto Mangunkusuno hospital (RSCM) and sensitivity pattern to antifungal. This retrospective study used patient medical record from 2011-2014. This study had 117 candidemia case in RSCM during 2011-2014. Every year candidemia was dominated by Candida tropicalis, Candida albicans, and Candida parapsilosis with trend the increase number of Candida tropicalis since 2013. Susceptibility pattern of Candida that cause candidemia in RSCM from 71 isolat tested the result was86% spesies Candida flukonazol sensitive, 99% vorikonazol sensitive, 97% amfoterisin B sensitive and 100% flusitosin sensitive.